Kualitas Produk, Harga, Terhadap Keputusan Pembelian melalui Kepuasan Pelanggan pada Heritage Fragrances - Gymnastiar Mustaqiim; Emil Salim; Della Asmaria Putri (GLOBAL SCIENTS PUBLISHER, 2026)
This research was conducted to understand how product quality and price influence the purchasing decisions of Heritage Fragrances customers, with customer satisfaction as an intervening variable. The study employed a quantitative approach using a survey method. A total of 100 Heritage Fragrances customers were selected as respondents through purposive sampling. The data were then analyzed using SmartPLS 4 software. The results of the analysis indicate that product quality has a significant and positive effect on customer satisfaction (β = 0.746; p < 0.001) and on purchasing decisions (β = 0.279; p = 0.005). Price was also found to have a significant and positive effect on customer satisfaction (β = 0.502; p < 0.001) as well as on purchasing decisions (β = 0.258; p = 0.001). In addition, customer satisfaction has a significant and positive effect on purchasing decisions (β = 0.502; p < 0.001). This study also found that customer satisfaction is able to mediate the relationship between product quality and purchasing decisions, as well as between price and purchasing decisions. Overall, the findings of this study demonstrate that improving product quality and setting prices that match customer expectations can increase customer satisfaction, which in turn encourages customers to make purchasing decisions at Heritage Fragrances.